Effect of trade liberalization on household welfare in Costa Rica during 1995–2006 - Chacón Romero, Sergio (2013)
In this article, we analyze the effect of trade liberalization, defined as reduction in tariffs, on household welfare during 1995-2006 in Costa Rica. This trade policy has a direct impact on tradable good prices, which indirectly affects non-tradable good prices and wages, changing household welfare. There is evidence of gains in welfare, as theory suggests, thanks to trade liberalization. However, the transmission was imperfect and low. The results also show that the welfare gains were not asymmetrical distributed since lowest income households and low and medium skilled workers were the most favored.